Integration of an energy balance snowmelt model into an open source modeling framework. (June 2015) - Sen Gupta, A.; Tarboton, D.G.; Hummel, P.; Brown, M.E.; Habib, S.
Abstract: This paper presents a data model for organizing the inputs and outputs of an energy balance snowmelt model (the Utah Energy Balance Model, UEB) that provides a foundation for its integration into the EPA BASINS modeling framework and enables its coupling with other hydrologic models in this system. Having UEB as a BASINS component has facilitated its coupling with the Geospatial Streamflow Forecast Model (GeoSFM) to compute the melting of glaciers and subsequent streamflow in the Himalayas. The data model uses a combination of structured text and network Common Data Form (netCDF) files to represent parameters, geographical, time series, and gridded space-time data. We describe the design and structure of this data model, integration methodology of UEB and GeoSFM and illustrate the effectiveness of the resulting coupled models for the computation of surface water input and streamflow for a glaciated watershed in Nepal Himalayas. Highlights: We developed a data model to structure the input and output of an energy balance snow and glacier melt model. A rainfall-runoff model was coupled with a snow and glacier melt model in EPA BASINS to enhance streamflow information. The model was applied to simulate streamflow using snow and glacier melt information in a high altitude Himalayan watershed.